THE IMPORTANCE OF ORGANIZING INNOVATION ACTIVITIES OF TEACHERS OF PRESCHOOL EDUCATIONAL ORGANIZATIONS - Turdieva Mokhira Jurakulovna (Western European Studies, 2024)
Today, this article describes the requirements of the state and society for teachers of preschool educational organizations, problems in implementing the assigned tasks and their solutions. Aspects that should be paid attention to when organizing innovative activities of teachers of preschool educational organizations are discussed
Keywords: teacher; educator; education system; state requirements